G380 Paediatric acute kidney injury is poorly recognised in the hospital setting. (27th April 2016) - Stojanovic, J; Bhojani, S; Melhem, N; Houtman, P; Singh, C; Ahmed, M; Hayes, W; Lennon, R; Taylor, D; Sinha, M; Milford, D
Abstract : Aims: Acute kidney injury (AKI) is a significant cause of morbidity and mortality among adult in-patients. High incidence and under-recognition has lead to the development of a national AKI programme. The aims of this study were to determine the incidence of AKI in a paediatric setting and to investigate recognition and management of AKI. This multi-centre project was supported by the British Association for Paediatric Nephrology. Methods: Creatinine measurements performed at six centres (3 tertiary and 3 district general hospitals) over a six-month period (01/07/12–31/12/12) were evaluated using the NHS AKI alert algorithm. Patients age 29 days to 17 years old were included. A subset of children were randomly selected for case note review. Information was obtained from paper and electronic patient notes. AKI stage 1 was defined as a rise of 1.5- <2x baseline creatinine level; AKI stage 2 a rise of 2- <3x baseline and AKI stage 3 a rise of >3x baseline. Results: 57, 278 creatinine measurements were analysed during the study period with 5325 (10.8%) AKI alerts in 1112 patients. There were AKI 1 (62%), AKI 2 (16%) and AKI 3 (22%) alerts during the study period. Age distribution: 222 (20%) <1y, 432 (39%) 1- <6y, 192 (17%) 6- <11y, 207 (19%) 11- <16y and 59 (5%) 16–17y. AKI 1 was the largest group across all ages and a third of all alerts were in children under 6y. There were no gender differences but significant differences between centres for AKI alerts. We reviewed case notes of 66 children (39 boys) aged between 29 days to 17 years, AKI was recognised by the treating physicians in 18 patients (27.3%). Of all patients, only 17% had a pre-existing renal condition and were known to nephrology. 30% of patients had urine tested and 66% had medication dosage adjusted to estimated GFR. Conclusions: Our data indicate that AKI remains clinically under-recognised in children and there is a need for education about its management. Timely recognition and optimal management of AKI is important to improve long term renal outcomes. Future investigations will aim to determine the impact of the NHS AKI alert algorithm